Integrative evidence reveals a new species of Hysterothylacium (Nematoda: Ascaridoidea), with the characterization of its complete mitochondrial genome - Hui-Xia Chen; Hai-Xia Qiao; Wen-Ting Zhao; Xiao-Hong Gu; Liang Li (International Journal for Parasitology: Parasites and Wildlife)
The genus Hysterothylacium (Ascaridida: Raphidascarididae) is among the commonest groups of parasitic nematodes occurring in the digestive tract of marine fishes. In the present study, a new species of Hysterothylacium, H. hainanense sp. n. collected from Uranoscopus tosae (Jordan & Hubbs) and U. japonicus Houttuyn (Perciformes: Uranoscopidae) in the Chinese waters was described using integrative methods, including light and scanning electron microscopy, and ASAP and BI analyses based on the ITS sequence data. The complete mitochondrial genome of the new species was sequenced and annotated, which represents the first mitogenomic data for the genus Hysterothylacium, and also for the family Raphidascarididae. The mitogenome of H. hainanense sp. n. is 14059 bp in length, including 12 protein coding genes (missing atp8), 22 tRNA genes, 2 rRNA genes and 2 non-coding regions, which has 67.0% of overall A + T content, and represents the lowest level of A + T content in the ascaridoid mitogenomes reported so far. Molecular phylogenetic results suggested a close affinity between H. hainanense sp. n. and H. fabri in the genus Hysterothylacium.